2005
DOI: 10.1007/s10597-005-5981-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Equivalence of Generic Clozapine

Abstract: There were no significant increases in mental health service utilization after the conversion to Mylan generic clozapine. The switch to Mylan generic clozapine was cost effective, as the reduction in pharmacy costs was not offset by increased utilization costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 5 publications
0
15
1
1
Order By: Relevance
“…These results were similar to previous studies, which showed no differences in terms of adverse events between the generic drug and brandname drugs of simvastatin, warfarin, and clozapine. [22][23][24][25][26] Nevertheless, in the present study, there was a trend of higher incidences of bitter taste and blurring with Cosopt, and a higher incidence of headache with Batidor in both groups, but without significant differences. In fact, there are no differences in terms of active ingredient, preservative (0.0075% benzalkonium chloride), pH (*5.65), and osmolarity (242-323 mOsM) between Cosopt and Batidor, based on data from the US Food and Drug Administration.…”
Section: Discussioncontrasting
confidence: 70%
“…These results were similar to previous studies, which showed no differences in terms of adverse events between the generic drug and brandname drugs of simvastatin, warfarin, and clozapine. [22][23][24][25][26] Nevertheless, in the present study, there was a trend of higher incidences of bitter taste and blurring with Cosopt, and a higher incidence of headache with Batidor in both groups, but without significant differences. In fact, there are no differences in terms of active ingredient, preservative (0.0075% benzalkonium chloride), pH (*5.65), and osmolarity (242-323 mOsM) between Cosopt and Batidor, based on data from the US Food and Drug Administration.…”
Section: Discussioncontrasting
confidence: 70%
“…Similarly, in two years of observation of 108 patients there were no differences in the duration of hospitalizations, the number of outpatient visits and median clozapine serum concentration between patients treated with the reference and generic drug. Moreover, in patients treated with the generic there have been statistically fewer emergency room admissions (Healy et al, 2005). In addition, there have been no observations of any significant clinical status worsening after introduction of a generic clozapine (Oluboka et al, 2010;Makela et al, 2003).…”
Section: Therapeutic Equivalence Of Antidepressant and Antipsychotic mentioning
confidence: 96%
“…In most of the studies no clinical deterioration, changes in the serum concentration of clozapine or decreased tolerance for the treatment was observed [15]However, some changes have been reported in the concentrations of the metabolite of clozapine, norclozapine, in patients who have been switched from the reference to generic drug [16]. Some patients needed higher doses of the generic formulation or including an additional antipsychotic [17]. Similar reports have been filed with regards to substituting the branded olanzapine and risperidone with generic formulations [18][19][20].…”
Section: Bioequivalence Studiesmentioning
confidence: 99%
“…Opisywano różnice w stężeniu metabolitu klozapiny -norklozapiny u chorych, u których dokonano zmiany leku referencyjnego na generyczny [16]. Część z pacjentów wymagała stosowania wyższych dawek leku generycznego lub włączenia dodatkowego leku przeciwpsychotycznego [17]. Podobne doniesienia dotyczyły zastą-pienia leków zawierających olanzapinę oraz risperidon [18][19][20].…”
Section: Badania Równoważności Biologicznejunclassified